2022
DOI: 10.1186/s12884-022-04685-0
|View full text |Cite
|
Sign up to set email alerts
|

Delayed secretory activation and low milk production in women with gestational diabetes: a case series

Abstract: Background Gestational diabetes mellitus (GDM) is major pregnancy complication that is associated with short- and long-term consequences for both mother and infant, including increased risk of diabetes later in life. A longer breastfeeding duration has been associated with a reduced risk of diabetes, however, women with GDM are less likely to exclusively breastfeed and have shorter breastfeeding duration. While the timing of breastfeeding initiation and milk removal frequency affects subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…Gestational diabetes mellitus (GDM) is the most common pregnancy complication and is increasing in prevalence globally [ 42 ]. A few studies have found that women with GDM are at greater risk of delayed secretory activation and LMS [ [43] , [44] , [45] ]. Insulin regulates the expression of genes involved in milk protein synthesis, including signal transducer and activator of transcription 5 (STAT5a) and E74-like factor 5, which are key components of prolactin signaling [ 46 , 47 ].…”
Section: Causes Of Lmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gestational diabetes mellitus (GDM) is the most common pregnancy complication and is increasing in prevalence globally [ 42 ]. A few studies have found that women with GDM are at greater risk of delayed secretory activation and LMS [ [43] , [44] , [45] ]. Insulin regulates the expression of genes involved in milk protein synthesis, including signal transducer and activator of transcription 5 (STAT5a) and E74-like factor 5, which are key components of prolactin signaling [ 46 , 47 ].…”
Section: Causes Of Lmsmentioning
confidence: 99%
“…Insulin regulates the expression of genes involved in milk protein synthesis, including signal transducer and activator of transcription 5 (STAT5a) and E74-like factor 5, which are key components of prolactin signaling [ 46 , 47 ]. Therefore, insulin resistance might be a potential mechanism underpinning the link between GDM and LMS that has been shown in a recent case series [ 43 ]. There is no doubt that pre-existing type 1 and type 2 diabetes mellitus (T1DM and T2DM) are also associated with poor breastfeeding outcomes [ 48 ].…”
Section: Causes Of Lmsmentioning
confidence: 99%
“…Milk production depends on the proper development of breast during pregnancy. Insulin metabolism controls milk secretion, supporting mammary gland differentiation [ 142 ]. Insulin upregulates genes related to mammary epithelial cell (MEC) proliferation and downregulates genes responsible for MEC differentiation [ 143 , 144 ].…”
Section: Diabetes Mellitus and Breastfeedingmentioning
confidence: 99%
“…In addition, numerous social, psychological, and behavioral factors are associated with early breastfeeding cessation [ 3 , 4 , 5 , 6 ]. Several studies reported associations between maternal metabolic conditions such as malnutrition [ 7 ], excessive maternal fat mass [ 8 ], and gestational diabetes [ 9 ] and milk supply. Moreover, we and others determined that genetic variations in genes critical for mammary gland function (i.e., prolactin ( PRL ) [ 10 ], prolactin receptor ( PRLR ) [ 11 ], ZnT2 ( SLC30A2 ) [ 12 ], and milk fat globule-epidermal factor 8 protein ( MFGE8 ) [ 13 ]) are associated with the ability to produce milk, providing evidence that biological factors are also responsible for low milk supply.…”
Section: Introductionmentioning
confidence: 99%